Differentiation of dendritic cells from different human circulating progenitors and effect of PPAR-gamma stimulation - Silvano, Angela; Paccosi, Sara; Bonetti, Maria Ida; Parenti, Astrid; Bosi, Alberto; Romagnoli, Paolo (Italian Journal of Anatomy and Embryology, 2018)
Dendritic cells (DCs) of the immune system include - among others - Langerhans cells (CD1a+, langerin/CD207+) and connective tissue DCs (DC-SIGN/CD209+). These cells can be generated in vitro from different precursors, but the results have been inconsistent and the differentiation of specific subtypes has been hard to achieve. Although DCs express PPAR- gamma, the expression of this receptor by DC precursors and the effect of its stimulation on DC differentiation are poorly known. This study has addressed the differentiation poten- tial into DCs of different precursors collected from peripheral blood of healthy adult human donors and the effect of rosiglitazone, an agonist of PPAR-gamma, on that differentiation.Upon immunomagnetic separation, CD14+ monocytes and CD34+ and CD133+ progeni- tors were cultured with cytokines for 8 d (CD14+) or 18 d (CD34+ and CD133+); rosiglitazone (1 μmol/l) was added in some experiments. All precursors generated HLA-DR+(high) DCs; those from CD34+ and CD133+ precursors were in part large and more rich in organelles, in part medium-sized and less rich in organelles. A proportion of cells, varying with the pre- cursors (CD14+<CD34+<CD133+), were CD1a+ and CD207+; in cells derived from CD34+ and CD133+ progenitors they were among the large ones. Many cells from any culture expressed CD209, also together with CD207. Rudimentary Birbeck granules were observed in few DCs from any precursor. Variable percentages of DCs, highest among those from CD133+ precur- sors, expressed CD80, CD83 and CD86. Rosiglitazone led to significant increase in CD207+ DCs among cells generated from CD133+ precursors; DCs derived from CD133+ precursors stimu- lated the proliferation of CD4+ lymphocytes much more than that of CD8+ ones and such pro- liferation was significantly reduced if DCs had been generated in the presence of rosiglitazone. Freshly isolated CD133+ cells showed a number of copies of mRNA for PPAR-γ higher than CD14+ and CD34+ cells. The results indicate that: the differentiation potential of hematopoietic cells into DCs with different phenotypes depends on the step reached by the precursors in vivo; the orientation towards Langerhans cells can begin very early; the differentiation in vitro does not mimic entirely that in vivo; the most immature progenitors, CD133+ cells, express PPAR- gamma; stimulation of these receptors may play a role in modulating DC differentiation.